2017
DOI: 10.1111/jfpe.12530
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐assisted extraction of oil from macauba pulp using alcoholic solvents

Abstract: Ultrasound‐assisted extraction (UAE) of macauba pulp oil was investigated using ethanol and isopropanol as solvents and compared with the conventional extraction technique. An experimental design was applied to evaluate the influence of the experimental variables (temperature, solvent to pulp ratio, and time) on the oil extraction and to optimize them. The optimum conditions were then evaluated in relation to the extraction kinetics and the effect of the application of ultrasound in the process was determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 40 publications
4
31
0
Order By: Relevance
“…Oils extracted with alcoholic solvents presented typical composition of macadamia oil, predominantly of monounsaturated fatty acids (approximately 80% of palmitoleic and oleic acids), which is in agreement with results of Aquino‐Bolaños et al In fact, the fatty acid profile of oils is not influenced by the type of solvent or the extraction method …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Oils extracted with alcoholic solvents presented typical composition of macadamia oil, predominantly of monounsaturated fatty acids (approximately 80% of palmitoleic and oleic acids), which is in agreement with results of Aquino‐Bolaños et al In fact, the fatty acid profile of oils is not influenced by the type of solvent or the extraction method …”
Section: Resultssupporting
confidence: 90%
“…Nevertheless, hexane presents in its composition n‐hexane (approximately 52%) which is considered neurotoxic, in addition commercial hexane contributes to environmental pollution and is flammable which carries the risk of explosions in the industry. Therefore, alternative solvents have been proposed, aimed to replace it, as example ethanol and isopropanol …”
Section: Introductionmentioning
confidence: 99%
“…A literature reported by Stevanato and da Silva () evaluated the extraction of radish seed oil at 45°C and 60 min and observed that increasing the solvent‐to‐seed ratio from 4:1 to 12:1 increased the oil yield from 17.10% to 23.22%, respectively. Another study reported an increase in the yield of macauba pulp oil (28.15%–30.70%) when increasing the relative amount of solvent from 6:1 to 10:1 (Rodrigues, Mello, dos Santos Garcia, & Silva, ). Extraction time is also an important variable which has been found to have the greatest influence on the radish seed oil ( Raphubus sativus L.) yield (da Silva, dos Santos Garcia, Arroyo, & da Silva, ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, as the temperature increased, the density and viscosity of solvent would decrease thus resulting in the increase of mass transfer which enhanced the oil recovery (Tian et al, ). Rodrigues et al () reported that higher temperature in the range of 40–60°C could promote the solubility of oil in alcoholic solvent. Other studies by de Mello et al () and Tavares, Massa, Gonçalves, da Silva, and dos Santos () observed that increasing the temperature from 40 to 60°C increased the yield of chia seeds oil and crambe seed oil respectively.…”
Section: Resultsmentioning
confidence: 99%